The Influence of Socioeconomic Level on the Verified Index of Agrarian Disputes - Rusmalinda, Sinta; Sudrajat, Ajeung Syilva Syara Noor Silmi; Mauliddin, Arif Iman; Putri, Nurul Askara (Scimadly Publishing, 2025)
This study aims to analyze the influence of socioeconomic factors on the involvement of Yadika Cicalengka High School/Vocational School alumni in agrarian disputes. Using a descriptive quantitative approach, the findings indicate a significant link between individuals' socioeconomic conditions and their likelihood of becoming involved in land conflicts. Alumni facing unstable economic situations tend to be more vulnerable to agrarian disputes, whether as victims or as participants. However, involvement in such disputes is not solely determined by socioeconomic factors, as government policy, limited access to legal information, and internal family conflicts also play important roles. These findings highlight the importance of improving legal literacy and economic empowerment among youth as preventive strategies to reduce the risk of agrarian conflict. Basic legal education and entrepreneurship training could help strengthen the socioeconomic resilience of the younger generation. This study is limited by its sample, which only includes alumni from a single educational institution, and does not explore qualitative factors that may influence involvement in conflicts. Future research is recommended to adopt a mixed-method approach and broader social and geographical coverage to gain a more comprehensive understanding.